2011
DOI: 10.1371/journal.pone.0027007
|View full text |Cite
|
Sign up to set email alerts
|

A Splice Isoform of DNedd4, DNedd4-Long, Negatively Regulates Neuromuscular Synaptogenesis and Viability in Drosophila

Abstract: BackgroundNeuromuscular (NM) synaptogenesis is a tightly regulated process. We previously showed that in flies, Drosophila Nedd4 (dNedd4/dNedd4S) is required for proper NM synaptogenesis by promoting endocytosis of commissureless from the muscle surface, a pre-requisite step for muscle innervation. DNedd4 is an E3 ubiquitin ligase comprised of a C2-WW(x3)-Hect domain architecture, which includes several splice isoforms, the most prominent ones are dNedd4-short (dNedd4S) and dNedd4-long (dNedd4Lo).Methodology/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…The metabolite ɣ-elemene is a sesquiterpene hydrocarbon that has antitumor activity notable for being efficient against several types of cancer (Costa et al, 2010). It has been reported that curzerene (an oxygenated sesquiterpene) has an antiproliferative effect on tumor cells (Costa et al, 2010;Zhong et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolite ɣ-elemene is a sesquiterpene hydrocarbon that has antitumor activity notable for being efficient against several types of cancer (Costa et al, 2010). It has been reported that curzerene (an oxygenated sesquiterpene) has an antiproliferative effect on tumor cells (Costa et al, 2010;Zhong et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination is carried out by E1, E2, and E3 enzymes, with the latter (E3 ubiquitin ligase) responsible for substrate recognition and attachment of ubiquitin. We previously identified the HECT E3 ubiquitin ligase Drosophila (d) Nedd4 as a regulator of NMS (8,9). Like other Nedd4 proteins, dNedd4 contains an N-terminal C2 domain, which in its mammalian orthologue Nedd4, is responsible for plasma membrane localization (10,11) and intramolecular inhibitory interactions with the catalytic HECT domain (12,13), 3 WW domains that usually recognize substrates by binding to PY motifs (L/PPXY) (8,14,15), and a C-terminal catalytic HECT domain (16,17).…”
Section: Neuromuscular Synaptogenesis (Nms)mentioning
confidence: 99%
“…In Drosophila, dNedd4 is present as two major splice isoforms: dNedd4-short (dNedd4S) and dNedd4-long (dNedd4Lo). These isoforms differ only in the presence of two unique regions in dNedd4Lo: a N-terminal region generated by an alternate start codon, and a Middle (Mid) region generated by an additional exon between the WW1 and WW2 domains (9). We previously showed that dNedd4S acts as a positive regulator of NMS in Drosophila, where it functions in the muscle to ubiquitinate and internalize Commissureless (Comm) from the muscle surface (8).…”
Section: Neuromuscular Synaptogenesis (Nms)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many other ubiquitin pathways also play important roles in a variety of aspects of synaptic development. To date, at least six different E3 ligase complexes were identified that regulate a variety of processes during synaptic development: (i) anaphase‐promoting complex/cyclosome restrains synaptic size by controlling the presynaptic Liprin‐α protein level at fly NMJs (van Roessel et al 2004), and regulates synaptic transmission by controlling the number of glutamate receptors postsynaptically in both Drosophila and C. elegans (Juo & Kaplan, 2004; van Roessel et al 2004), and controls axon growth and patterning in mice (Konishi et al 2004); (ii) presynaptic‐membrane‐associated SCF E3 complex containing the F‐Box protein Scrapper regulates synaptic vesicle release by targeting RIM1 in mice (Yao et al 2007), and the fly Scrapper is expressed as a nerve‐membrane‐associated protein (unpublished observation), but whether it also downregulates RIM1 remains unclear; (iii) F‐Box protein SEL‐10 works in a SCF E3 complex to control synaptic elimination and stabilization in C. elegans (Ding et al 2007); (iv) postsynaptic lin‐23 containing SCF E3 and a KEL‐8/Cullin‐3 E3 regulate the abundance of the C. elegans AMPA‐type glutamate receptor (Dreier et al 2005; Schaefer & Rongo, 2006); (v) short isoform of fly Nedd4, a HECT E3 ubiquitin ligase, regulates NMJ formation by promoting ubiquitination and internalization of Commissureless (Comm), while a long isoform of Nedd4 plays an inhibitory role in NMJ formation (Ing et al 2007; Zhong et al 2011); and (vi) F‐Box protein, Mec‐15, functions in parallel with the RPM‐1 pathway in worm touch receptor neurons to promote synaptic formation and development (Bounoutas et al 2009).…”
Section: Introductionmentioning
confidence: 99%